Pemberian senam low-impact untuk meningkatkan kadar hemogloblin pada lanjut usia dengan anemia di Dusun Bugel, Mojolaban, Sukoharjo - Widiyono, Widiyono; Putra, Fajar Alam; Eriyanti, Etty; Sumarni, Ranti Ningsih; Indriyati, Indriyati (JOURNAL OF Public Health Concerns, 2025)
Background: The elderly population is those aged 60 years and over. The compensation that the body has with the elderly who experience anemia is by increasing the heart's pumping power to meet the needs of blood throughout the body by increasing the heart's pumping power. One of the interventions that can be given is providing low-impact gymnastics. Purpose: Provide low-impact gymnastics training to increase hemoglobin levels in the elderly who suffer from anemia. Method: The activity of providing low-impact gymnastics is designed to equip anemia sufferers in preventing complications of anemia. The activity was carried out in Bugel Hamlet, Mojolaban, Sukoharjo. The training was carried out in collaboration with the nursing study program at Sahid University Surakarta, one of the courses of which is medical surgical nursing and community nursing. The number of elderly who participated in this activity was 20 participants. Participants received health education related to anemia and Hb examinations before and after low-impact gymnastics. Results: This low-impact gymnastics community service activity ran smoothly and orderly and the participants were quite enthusiastic about following the course of the activity. Hb measurements showed that the proportion of anemia categories before routine low-impact aerobic exercise intervention was spread across the low category of 5 people (25.0%), medium of 5 people (25.0%) and normal of 10 people (50.0%), while the proportion of categories after elderly exercise experienced changes in Hb levels were all in the normal category of 20 people (100.0%). Conclusion: Physical activity and one of them is low-impact aerobic gymnastics which is done regularly and routinely can increase hemoglobin (Hb) levels in the elderly. Suggestion: The need for family and community support to play an active role in providing guidance and assistance to carry out appropriate physical activity activities for the elderly in maintaining health. Keywords: Elderly; Hemoglobin; Low-impact gymnastics Pendahuluan: Penduduk lansia adalah mereka yang berusia 60 tahun ke atas. Kompensasi yang dimiliki tubuh dengan lansia yang mengalami anemia yaitu dengan meningkatnya daya pompa jantung untuk memenuhi kebutuhan darah keseluruh tubuh dengan meningkatnya daya pompa jantung. Intervensi yang dapat diberikan salah satunya pemberian senam law impact. Tujuan: Memberi pelatihan senam low-impact untuk meningkatan kadar hemoglobin pada lansia yang menderita anemia. Metode: Kegiatan pemberian senam low-impact dirancang untuk membekali para penderita anemia dalam mencegah komplikasi penyakit anemia. Kegiatan dilaksanakan di Di Dusun Bugel, Mojolaban, Sukoharjo. Pelatihan dilaksanakan atas kerja sama dengan prodi keperawatan Universitas Sahid Surakarta yang salah satu mata kuliahnya adalah keperawatan medikal bedah dan keperawatan komunitas. Jumlah lansia yang mengikuti kegiatan ini ada 20 peserta. Peserta mendapatkan penyuluhan kesehatan terkait anemia dan pemeriksaan Hb sebelum dan sesudah senam low-impact. Hasil: Kegiatan pengabdian kepada masyarakat senam low-impact ini berjalan lancar dan tertib dan peserta cukup antusias mengikuti jalannya kegiatan. Pengukuran Hb menunjukkan proporsi kategori anemia sebelum intervensi rutin senam aerobik low-impact tersebar pada kategori rendah sebanyak 5 orang (25.0%), sedang sebanyak 5 orang (25.0%) dan normal sebanyak 10 orang (50.0%) sedangkan proporsi kategori setelah senam lansia mengalami perubahan kadar Hb seluruhnya berada pada kategori normal 20 orang (100.0%). Simpulan: Aktivitas fisik dan salah satunya adalah senam aerobic low-impact yang dilakukan secara teratur dan rutin dapat meningkatkan kadar haemoglobin (Hb) pada lansia. Saran: Perlunya dukungan keluarga dan komunitas untuk berperan aktif memberikan bimbingan dan pendampingan untuk melakukan kegiatan aktifitas fisik yang sesuai pada lansia dalam menjaga kesehatan.